The Proposed Banning of Alcohol Advertising in a Developing Economy - Govender, Jeevarathnam Parthasarathy (Journal of Economics and Behavioral Studies, 2013)
The growing problem of alcohol misuse and its social consequences have been attributed to the advertising of alcohol, by some parties. Alcohol companies and the advertising industry have refuted this claim. It is against this background that this paper seeks to assess consumer attitudes towards alcohol advertising in South Africa. A survey was conducted amongst a sample of 400 respondents. Respondent demographics and attitudes towards the advertising of alcohol were ascertained. The results indicate no significant relationship between the selected demographic variables (viz. gender, age, income, education level and race) and attitude towards the advertising of alcohol. Some perspectives on the implications for policy and practice are presented.